Elements of power systems - Sadhu, Pradip Kumar; Das, Soumya (CRC Press, 2016)
"Elements of power systems prepares students for engineering degrees, diplomas, associate member of the Institution of Engineers (AMIE) examinations, or corresponding examinations in electrical power systems. Complete with case studies, worked examples, and circuit schematic diagrams, this comprehensive text provides a solid understanding of the theoretical aspects of power system engineering, instills a practical knowledge of large-scale power system analysis techniques, covers load characteristics, tariffs, power system stability, and more. Elements of Power Systems is designed as an undergraduate-level textbook, but the book also makes a handy reference for practicing power engineers." -- Back cover